Mental Illness in the Community / The Pathway to Psychiatric Care - Goldberg David; Huxley Peter (Tavistock Publications, 1980)
The authors offer suggestions for further improvements in detection and care of the mentally ill, arguing that professionals such as social workers, specialized nurses, and clinical psychologists can make valuable contributions to work in the primary care setting. Acknowledgements, Foreword, Introduction, Level 1: Mental Illness in the Community, The First Filter: The Decision to Consult, Level 2 and the Second Filter: Psychiatric Disorders Among Primary Care Attenders, Level 3: Conspicuous Psychiatric Morbidity in Primary Care Settings, The Third Filter: Referral to Psychiatric Services, Levels 4 and 5: Psychiatric Morbidity Treated by Psychiatrists, Interview Techniques in Primary Care Settings, Non-Medical Models of Care, Overview, References, Name and Subject Index.